2009
DOI: 10.1089/tmj.2009.0030
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction with Physician–Patient Communication During Telemedicine

Abstract: The quality of physician-patient communication is a critical factor in treatment outcomes and patient satisfaction with care. To date, few studies have specifically conducted an in-depth evaluation of the effect of telemedicine (TM) on physician-patient communication in a medical setting. Our objective was to determine whether physical separation and technology used during TM have a negative effect on physician-patient communication. In this noninferiority randomized clinical trial, patients were randomized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
180
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(200 citation statements)
references
References 32 publications
13
180
1
6
Order By: Relevance
“…Other research have also reported a lower number of patients utterances (9) and mastery of the professional on communication (10) during consultations.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Other research have also reported a lower number of patients utterances (9) and mastery of the professional on communication (10) during consultations.…”
Section: Discussionmentioning
confidence: 83%
“…This kind of counseling occurs in a very small proportion in health consultations as professionals worry more about getting information on psychosocial and biomedical content both in face to face consultations and in teleconsultations (10,26) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Expansion of telehealth in VA is likely to enable timely access to care (Agha et al, 2009;Wakefield et al, 2004;Whited et al, 2002;Whited et al, 2004;Wilkins, Lowery, & Goldfarb, 2007) in several different ways. Clinical video telehealth can facilitate contact between distant patients and providers and is particularly useful for patients in rural or otherwise underserved areas who face transportation barriers, poverty, and limited access to specialty care .…”
Section: Discussionmentioning
confidence: 99%